Outer limits the filmgoers' guide to the great science-fiction films - Hughes, Howard 1971- (I.B. Tauris, 2014)
Howard Hughe's new filmgoers' guide to science-fiction films delves deep into the landmark movies of this ever popular genre, from Metropolis to Avatar and beyond, and covers over 250 more. It explores science-fiction cinema through 26 great films, from the silent classic Metropolis to today.